Enhancing the Role of Public Prosecutors in Maintaining Legal Certainty - Sajimin Sajimin; Anang Shophan Tornado; Rahmida Erliyani; Elman Azizov (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
Legal certainty (rechtssicherheit) is a fundamental pillar of the Rule of Law, ensuring that legal provisions are clear, consistent, and predictable. In the Indonesian criminal justice system, the Public Prosecutor holds a central position as the Dominus Litis (the master of the suit), possessing the exclusive authority to determine which cases proceed to court. However, the current implementation of prosecutorial authority often leans towards rigid legal positivism, creating a paradox where procedural certainty is achieved at the expense of substantive justice. Disparities in prosecution demands for similar crimes often lead to public distrust and legal uncertainty for justice seekers. Furthermore, prosecutors often lack the cognitive flexibility to handle complex cases that require discretionary wisdom. This study aims to analyze the challenges in maintaining legal certainty and proposes a strategy to enhance the prosecutor's role through the integration of Restorative Justice and a reform in prosecutorial competency. The research employs a normative juridical method with statutory and conceptual approaches, analyzing Attorney General Regulation No. 15 of 2020. The study finds that enhancing legal certainty requires shifting the paradigm from